Reading Rate in Informational Text: Norms and Implications for Theory and Practice in the Primary Grades. Issue 3 (3rd April 2019) - Tortorelli, Laura S.
Abstract : The purpose of this study was to explore reading rates in informational text for children in the primary grades (1–3) by analyzing a large, preexisting statewide dataset ( n  = 21, 005). The results indicated that children in the primary grades read informational text at approximately two-thirds the rates that would be anticipated based on previous studies, and that these reading rates increased sporadically and slowly over the course of the school year. In addition, when cut scores or minimum rates from previous studies were applied to this sample, one-half to three-fourths of all students were identified as at-risk. Alternative norms for reading rate in informational text in grades 1–3 are provided, and implications for theory and practice are discussed.